Sharia economics students’ anxiety towards mathematical economics course - Annisa Dwi Kurniawati (International Journal on Teaching and Learning Mathematics, 2019)
Mathematical economics is one of the compulsory courses in sharia economics students. At each exam of the mathematical economics course, the majority of scores earned by students tend to be low. It is the anxiety of facing the exam on mathematical economics courses that are considered as one of the causes. This type of research is qualitative descriptive research. The study aims to find out anxiety students have on the course of mathematical economics. The research subject is sharia economics students of IAIN Ponorogo who is taking a course in mathematical economics. The triangulation techniques of interviews, observations, and documentation are done for data retrieval. The results showed that student anxiety towards mathematical economics courses tends to be high. Some reasons for students' anxiety are educational backgrounds that are social majors, anxiety on low test scores, anxiety on the character of the lecturer, and anxiety caused by low self-efficacy in the ability to solve mathematical economics problems. From the results of this research, the lecturer is expected to be a motivator and mediator for students to reduce students' anxiety towards the courses of mathematical economics.